Interactive effects of modified tall oil and fat source on growth performance and carcass characteristics of finishing barrows and gilts - Woodworth, J.C.; O'Quinn, P.R.; Waylan, A.T.; Sawyer, J.T.; Goodband, Robert D.; Unruh, John A.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 144 pigs (initially 90 lb) was used to determine the interactive effects of fat source: none (NF), 6% choice white grease (CWG), or 6% poultry fat (PF); modified tall oil (MTO, 0 or .5%); and sex (barrows or gilts) on growth performance and carcass characteristics. Regardless of fat source, MTO improved belly firmness but did not influence growth performance. Gilts were leaner, had increased loin muscle area, and had softer bellies compared to barrows. Added fat decreased ADFI and improved F/G. Pigs fed PF had the best F/G, but the fattest carcasses and softest loins and bellies.
Keywords: Swine; Finishing pigs; Fat; Modified tall oil